An Analysis on the Implementation of Industrial Training for Mechanical Engineering Students in Uniten - S, Meenaloshini; C, Linda; H, Zaimah; M, Noor Zaimah (International Journal of Asian Social Science, 2014)
This paper examines the implementation of industrial training programme for Bachelor of Mechanical Engineering in Universiti Tenaga Nasional. The main objective of industrial training is to expose students to the real working environment of an engineering profession. It is also believed that through the industrial training programme, industries can contribute towards enhancing the learning process of students. In addition, it helps the universities and industries to develop stronger links and collaboration between them such as in research and development. Our experience shows that about 40% of the students carried out their industrial training in the manufacturing sector, 20% in power utilities, while the other 40% in other sectors such as oil and gas, service and maintenance, engineering consultancy, and automotive industry. Feedbacks for the host supervisors from the industries indicate that the students are very productive and efficient. Our assessment also shows that at least 90% of the students are excellent in accomplishing the industrial training programme. Feedbacks form faculty members who visited the students on site were also gathered and analyzed. Finally, this paper will also highlight some pertinent views and recommendations from the host companies for further improvement of the industrial training programme.